Studies on Etiology of Decline/Drying in Bael Plants - Singh, M.; Sharma, Sushil; Yadav, S. S.; Gaur, Ram Karan; Kumar, Mukesh (Indian Forester, 2017)
Studies were undertaken to establish the cause of decline/drying/wilting in bael plants from 2008 to 2014 which included different factors viz., nutritional, physiological, epidemiological, entomological and pathological. Perusal of pooled data of seven years showed that the organic carbon content of soils was low and ranged from 0.12 to 0.20 and 0.11 to 0.19 per cent in soil of diseased and healthy plants, respectively. In general, it decreased with increasing soil depths. The available phosphorus content varied from 6.67 to 9.06 kg ha-1 in soils of healthy plants and 6.67 to 8.63 kg ha-1 in soil of diseased plant and was low at all soil depths. The available copper, manganese and boron were sufficient in all depths of both soils collected from the rhizosphere of healthy and diseased plants. The DTPA extractable zinc was 0.89 ppm in soil of diseased plants and 0.76 ppm in soils of healthy plants at 0-30 cm depth and decreased with soil depth however it was in deficient range at 45-60 cm, 60-90 cm and 90-120 cm depth in soil of diseased plants. The DTPA extractable Fe was found to be deficient in both the samples of soils at 60-90 cm and 90-120 cm depth. The N, P and K content of healthy bael leaves were 1.20, 0.14 and 1.19 per cent where as it was 0.90, 0.08 and 1.02 per cent in leaves of diseased plants. The Zn, Cu, Mn, Fe and B content of leaves of healthy and diseased plants were in sufficient range, however, these content were higher in healthy leaves as compared to diseased leaves. The highest drying in bael trees was recorded during May - June and September - October beyond which incidence reduced gradually. Root borers, Acanthophorus rugiceps (2-3/plant of 115 mm length) were observed during 2011, 2012 and 2014 at a depth of 2 to 3 ft indicating possible association with the drying of plants. Gliocladium catenulatum, G. penicillioides, Rhizoctonia bataticola and Fusarium solani were isolated from roots of diseased plants and the pathogenicity with regard to F. solaniwas proved.